National Literacy Movement Policy and the Role of Literacy Communities in Human Development: Evidence from Lombok - Vince Tebay (PT FORMOSA CENDEKIA GLOBAL, 2023)
The tourism industry on the island of Lombok has influenced aspects of local culture, including the shifting of cultural values to commodity values. The literacy community then grows because of the concern of intellectual circles about the lack of literacy. This study uses a literature review approach. Primary data comes from observations, while secondary data is collected through journals, books, and articles. Data analysis was performed by connecting the data systematically and reflecting during the study. The validity of the data is measured by an external audit. The results showed that the interaction of the literacy community formed a variant of strategies for adaptation.